Elaboration and thermomechanical characterization of ceramic-based on Moroccan geomaterials: Application in construction. (2020) - Harrati, Achraf; Manni, Ahmed; El Bouari, Abdeslam; El Amrani El Hassani, Iz-Eddine; Sadik, Chaouki
Abstract: This work is based on the valorization and characterization of Moroccan geomaterials (MG) in the ceramic field. The raw materials (Kaolinitic clay of Oulmes: (KC); Red clay of Safi: (SC); Marl of Fez: (FM); Andalusite rich Schists of Oulmes: (AS); Magnesite of Boudkek: (Mag)) have been selected and characterized in terms of chemical, mineralogical composition, and thermal behavior wherein performed. The sintered ceramics (up to 1400 °C) resulted from these natural substances were tested mainly by physical, mechanical, and synthesized phase composition, as well as microstructural analysis, to determine their characteristics. As a result, the ceramic materials based on mullite and periclase have been obtained and confirmed by the X-ray diffraction and the scanning electron microscopy.